Communication Strategies of Islamic Boarding School in Managing Public Trust: ACADA-Based Qualitative Study in Indonesia - Dyatmika, Teddy; Alia Bihrajihant Raya; Muzayyanah, Mujtahidah Anggriani Ummul (Indonesian Journal of Advanced Research, 2026)
Negative media coverage has made effective communication essential for maintaining public trust in Islamic boarding schools. This qualitative study analyzes pesantren communication strategies using the Assessment, Communication Analysis, Design, and Action (ACADA) model through in-depth interviews with 25 school managers and parents. The findings show that communication success depends on message relevance, communicator credibility—especially Kyai involvement—appropriate media selection, digital system integration, and message intensity. The study recommends strengthening governance through digital media integration, two-way communication, student monitoring applications, consistent positive content, and improved human resource competence. These findings offer practical guidance for pesantren leaders and policymakers to build transparent, accessible, and trust-enhancing communication systems.